Combined venomics, venom gland transcriptomics, bioactivities, and antivenomics of two Bothrops jararaca populations from geographic isolated regions within the Brazilian Atlantic rainforest - Gonçalves Machado, Larissa (2016)
Bothrops jararaca is a slender and semi-arboreal medically relevant pit viper species endemic to tropical and subtropical forests in southern Brazil, Paraguay, and northern Argentina (Misiones). Within its geographic range, it is often abundant and is an important cause of snakebite. Although no subspecies are currently recognized, geographic analyses have revealed the existence of two well-supported B. jararaca clades that diverged during the Pliocene ~ 3.8 Mya and currently display a southeastern (SE) and a southern (S) Atlantic rainforest (Mata Atlântica) distribution. The spectrum, geographic variability, and ontogenetic changes of the venom proteomes of snakes from these two B. jararaca phylogroups were investigated applying a combined venom gland transcriptomic and venomic analysis. Comparisons of the venom proteomes and transcriptomes of B. jararaca from the SE and S geographic regions revealed notable interpopulational variability that may be due to the different levels of population-specific transcriptional regulation, including, in the case of the southern population, a marked ontogenetic venom compositional change involving the upregulation of the myotoxic PLA2 homolog, bothropstoxin-I. This population-specific marker can be used to estimate the proportion of venom from the southern population present in the B. jararaca venom pool used for the Brazilian soro antibotrópico (SAB) antivenom production. On the other hand, the southeastern population-specific D49-PLA2 molecules, BinTX-I and BinTX-II, lend support to the notion that the mainland ancestor of Bothrops insularis was originated within the same population that gave rise to the current SE B. jararaca phylogroup, and that this insular species endemic to Queimada Grande Island (Brazil) expresses a pedomorphic venom phenotype. Mirroring their compositional divergence, the two geographic B. jararaca venom pools showed distinct bioactivity profiles. However, the SAB antivenom manufactured in Vital Brazil Institute neutralized the lethal effect of both venoms to a similar extent. In addition, immobilized SAB antivenom immunocaptured most of the venom components of the venoms of both B. jararaca populations, but did not show immunoreactivity against vasoactive peptides. The Costa Rican bothropic–crotalic–lachesic (BCL) antivenom showed the same lack of reactivity against vasoactive peptides but, in addition, was less efficient immunocapturing PI- and PIII-SVMPs from the SE venom, and bothropstoxin-I, a CRISP molecule, and a D49-PLA2 from the venom of the southern B. jararaca phylogroup. The remarkable paraspecificity exhibited by the Brazilian and the Costa Rican antivenoms indicates large immunoreactive epitope conservation across the natural history of Bothrops, a genus that has its roots in the middle Miocene. This article is part of a Special Issue entitled: Omics Evolutionary Ecolog